FAKTOR-FAKTOR YANG MEMPENGARUHI PILIHAN KARIR MAHASISWA AKUNTANSI DI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS ISLAM MALANG - Liria Rhosa Effendi; Nur Hidayati; Muhammad Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe purpose of this study was to analyze how much influence fromintrinsic motivation, extrinsic motivation and parental influence on careerchoices as a Public Accountant and Corporate Accountant for accountingstudents and students at the Faculty of Economics and Business, Malang IslamicUniversity. Data sources used in this study are primary data. Data collectionmethod by distributing questionnaires. The data analysis method used ismultiple linear regression. The results showed that those who have influence onstudents and students when choosing a career as a Public Accountant areextrinsic motivation while those who have influence on students and studentswhen choosing their career as a Corporate Accountant are the influence ofparents.Keywords: Parental Influence, Extrinsic Motivation, Intrinsic Motivation, PublicAccountants, Students, and Corporate Accountants, Careers.